A Reductive Supramolecular Hydrogel: A Platform for Facile Fabrication of Diverse Metal‐Nanoparticle‐Decorated Conductive Networks with Spatiotemporal Control. Issue 8 (9th July 2020) - Wang, Peng; He, Guokang; Ji, Jingwei; Li, Jian; Zhou, Kang; Tian, Li; Feng, Kai; Sun, Fuwei; Li, Guangtao
Abstract: Nanoparticle‐hydrogel hybrid composites have a great potential for a broad range of applications, such as antibacterial materials, stimuli‐responsive materials and catalysis. A novel supramolecular hydrogel system was developed using an amino acid based amphiphile containing a terminal pyrrole moiety as a gelator. The pyrrole moiety could serve as both reducing agent and monomer, and a variety of metal precursors penetrating into the hydrogel could be reduced in situ into metal nanoparticles while the pyrrole moieties preorganized in hydrogel were oxidized into polyprroles, affording metal‐nanoparticle‐decorated covalent conductive networks. This strategy allows the facile fabrication of diverse mono‐ or multimetallic nanoparticle‐polymer networks from one hydrogel by a simple reaction‐diffusion approach. More importantly, besides homogeneous composites, unique multisegment heterogeneous systems with spatiotemporal control were also easily accessible. Furthermore, based on the same multifunctional molecule, the fabrication of hierarchically pore‐structured metal‐nanoparticles‐polymers as well as metal‐nanoparticles‐carbon structures was also realized. Abstract : Gelling together : A supramolecular hydrogel system using an amino acid based amphiphile containing a terminal pyrrole moiety as a gelator was developed. A variety of metal precursors penetrating into the hydrogel could be reduced in situ into metal nanoparticles while the pyrrole moieties were oxidized into polyprroles. This strategy allows for facile fabrication of diverse metal‐nanoparticle‐decorated covalent conductive networks as well as multisegement heterogeneous systems with spatiotemporal control.